Violet Wurfel ASEAN Lecture Series: Social Movements in Thailand - Tejapira, Kasian (Kasarinlan: Philippine Journal of Third World Studies; Vol 23 No 1 (2008): Contentious Politics)
I will proceed to give you the attempts of four different political forces to bridge the gap between the urban-rural divide during the Thai modern political history. These political forces are the Communist Party of Thailand, the student movement, the monarchy, and the Thai Rak Thai party of former Prime Minister Thaksin Shinawatra.
Keywords: urban-rural divide, social movements, Thailand, Communist Party of Thailand, monarchy, Thai Rak Thai